Exploring future perspectives and pipeline progression in vaccine research and development - Vecchio, Riccardo; Gentile, Leandro; Tafuri, Silvia; Costantino, Claudio; Odone, Anna (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The COVID-19 pandemic had a profound impact on vaccines’ Research and Development, on vaccines’ market, and on immunization programmes and policies. The need to promptly respond to the health emergency boostered resources’ allocation and innovation, while new technologies were made available. Regulatory procedures were revised and expedited, and global production and distribution capacities significantly increased. Aim of this review is to outline the trajectory of research in vaccinology and vaccines’ pipeline, highlighting major challenges and opportunities, and projecting future perspectives in vaccine preventables diseases’ prevention and control. Study Design. Narrative review. Methods. We comprehensively consulted key biomedical databases including “Medline” and “Embase”, preprint platforms, including”MedRxiv” and “BioRxiv”, clinical trial registries, selected grey literature sources and scientific reports. Further data and insights were collected from experts in the field. We first reflect on the impact that the COVID-19 had on vaccines’ Research and Development, regulatory frameworks, and market, we then present updated figures of vaccines pipeline, by different technologies, comparatively highlighting advantages and disadvantages. We conclude summarizing future perspectives in vaccines’ development and immunizations strategies, outlining key challenges, knowledge gaps and opportunities for prevention strategies. Results. COVID-19 vaccines’ development has been largely supported by public funding. New technologies and expetited authorization and distribution processes allowed to control the pandemic, leading vaccines’ market to grow exponentially. In the postpandemic era investments in prevention are projected to decrease but advancements in technology offer great potential to future immunization strategies. [....]